The Effect of ESG (Environmental, Social, and Governance) Practices on the Performance and Well-Being of Lecturers at Private Universities in Indonesia - Firdaus Aziz; Ansari; Astuti; Husen Bahasoan (Penerbit Jurnal Indonesia, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) practices on the performance of lecturers at private universities in Indonesia, with lecturer well-being considered as a mediating factor. Growing attention to sustainability in higher education has raised questions about how institutional governance and social responsibility influence academic staff outcomes. The objective of this research is to analyze whether ESG practices improve lecturers’ performance directly and indirectly through their well-being. A quantitative causal explanatory design was employed. Primary data were collected through questionnaires from 120 lecturers at private universities selected using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling to evaluate both measurement and structural models. The results indicate that ESG practices have a positive and significant effect on lecturer performance and lecturer well-being. In addition, lecturer well-being significantly mediates the relationship between ESG practices and performance. These findings highlight the importance of ESG for lecturer welfare.